Імплементація комплексної системи оцінювання ефективності інноваційної діяльності підприємств будівельної галузі - Глухова, Світлана Вячеславівна; Кильницька, Євгенія Володимирівна (Сумський державний університет, 2017)
У статті представлено впровадження авторської методики комплексної системи оцінювання ефективності інноваційної діяльності на підприємствах будівельної галузі. В роботі подано результати оцінювання інноваційної діяльності як за інтегральними, так і проміжним показниками. Результати оцінювання ефективності інноваційної діяльності досліджуваного підприємства інтерпретовано за допомогою відповідної розробленої системи, що дало змогу сформувати ґрунтовні висновки.

The aim of the article. The article is an application developed by the author of a comprehensive assessment system efficiency innovation on enterprises of the construction industry. The results of the analysis. The implementation of the author's technique of complex system of evaluation of efficiency of innovative activity in the construction industry enterprises is presented in the article. The developed system is based on the author's vision of innovation as a fundamentally new product for the market, and represents a set of strategic directions for evaluation to the variation formulation of criteria and indicators, that are synthesized by means of integral. For its adequate application of analyzed enterprises of the construction industry and identified the most innovative active. This has allowed to choose the object of research. In accordance with the procedure of the assessment established features of innovative activity of the enterprise under study, the type of innovation, degree of radicalism and the range of its influence on the activity of the enterprise as a whole. To ensure the most objective assessment of the criterion and its content database indexes are formed in accordance with the nature and specifics of the enterprise product innovation. The results of evaluations of innovative activity both integral and the intermediate indicators are submitted in the article. The results of estimation efficiency of innovative activity of the investigated companies are interpreted using the appropriate developed system, making it possible to form solid conclusions. Conclusions and directions of further researches. The experimental introduction authoring system for evaluating the effectiveness of innovation construction companies proved its effectiveness and practical significance. The tool provides an unambiguous assessment and objective assessment results, which will allow construction companies to effectively organize innovation and respond to changing internal and external environment. Presented author development are not only practical, but also a scientific perspective, which will be reflected in further studies, namely - development of the strategic direction of construction enterprises and related control systems innovation. Advantages of authoring development are: taking into account the interests of all stakeholders in the implementation of innovation sides in aspect of contributions and received benefits; the flexibility of the system during the formation of criteria base and component indicators according to the type of innovation and internal needs of subject assessment to analytical data; accurate the formalization of the results based on their single mathematical measurement; detailed structuring of performance evaluation as part of the criteria and focus areas, which allows the definition of "problem areas" in the implementation of innovation and identifying potential opportunities of innovation; the possibility formation of precise unequivocal conclusion on the effectiveness of innovative activity as each of the target areas and individual components of the system; compliance methodological tools system of evaluation advanced features of construction enterprises.
Implementation of integrated system evaluation efficiency of innovative activity of construction enterprises
Keywords: оцінка; інноваційна діяльність; ефективність; будівельні підприємства; інтегральній показник; evaluation; innovation; efficiency; construction companies; integrated indicator